Profiling online self-representation for cyber forensics: Anonymity and ageism in cyberspace / Dianne Lee Mei Cheong and Louis Sanzogni - Cheong, Dianne Lee Mei; Louis, Sanzogni (Institute of Research Management Innovation (IRMI), 2016)
Cyberspace offers ample opportunity where gender and age can lose their meaning with the influence of ageism. Online self-representation usually begins with a created gendered avatar followed by age identity. Empirical social data comprising surveys, random comments, and texts of 127 respondents were analyzed both quantitatively and qualitatively. The analysis showed that anonymity was assumed differently with eight possible reasons as gender was transferred online. Ageism experience was also identified differently by both male and female. A profile on online self representation for cyber forensics was subsequently established based on gender and age identity in addition to avatars. The findings have some forensic use as avatars layered with anonymity and ageism which facilitate some degree of self disclosure due to similarity in belief values, and attitudes to the users.